2011
DOI: 10.1007/s00044-011-9597-1
|View full text |Cite
|
Sign up to set email alerts
|

QSAR studies of aminopeptidase N/CD13 (APN) inhibitors with the scaffold 3-phenylpropane-1,2-diamine and molecular docking

Abstract: 3-D QSAR studies were conducted using a series of 39 compounds obtained in our laboratory to inhibit aminopeptidase N/CD13 (APN) for developing highly potent antitumor agents. Among constructed 3-D QSAR models, the best q 2 is 0.664 and the best r 2 is 0.995. Henceforth, the best 3-D QSAR model was applied for further chemical modification and optimization. Therefore, seven molecules were designed, and their activity values were predicted by the generated model. Their binding modes were elucidated by docking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…While overviewing the previously performed QSAR studies [60][61][62][63][64][65][66][67][68][69], it is observed that there are a few common features present namely electronegative and electropositive substitutions, hydrophobicity, steric properties, molecular symmetry, atomic masses and hydrogen bond donor-acceptor features which are responsible for the fluctuation in the potency of the APN inhibitors. Our previous study on 175 diverse set of APN inhibitors [63] disclosed that a few molecular features of the APN inhibitors namely the positive ionizable, hydrogen bond donor-acceptor and ring aromatic features of molecules are some of the important molecular features have important roles in determining the APN inhibitory activity of these molecules [63].…”
Section: Comparison Of the Previously Performed Qsar Studies With Thementioning
confidence: 99%
“…While overviewing the previously performed QSAR studies [60][61][62][63][64][65][66][67][68][69], it is observed that there are a few common features present namely electronegative and electropositive substitutions, hydrophobicity, steric properties, molecular symmetry, atomic masses and hydrogen bond donor-acceptor features which are responsible for the fluctuation in the potency of the APN inhibitors. Our previous study on 175 diverse set of APN inhibitors [63] disclosed that a few molecular features of the APN inhibitors namely the positive ionizable, hydrogen bond donor-acceptor and ring aromatic features of molecules are some of the important molecular features have important roles in determining the APN inhibitory activity of these molecules [63].…”
Section: Comparison Of the Previously Performed Qsar Studies With Thementioning
confidence: 99%
“…Therefore, model 1 was selected as the best MIFs model. Compared with the QSAR results of literature, our 3D-QSAR modeling have good predictive ability (Zhu et al, 2008;Xu et al, 2012).…”
Section: Molecular Docking and MD Simulationsmentioning
confidence: 65%